Estética práctica en John Martin: una mirada desde la filosofìa expresiva - autor, Sin (Arte, Individuo y Sociedad, 2008)
This paper propose to create a practice method that suggest a relationship between arts-philosophy and expression as a vortices of a new aesthetical hermeneutics analysis. In this way, the building of a conscience in an individual gives new alternatives to create knowledge. Reception analysis and expressive philosophy are a new horizon as a methodology of a personal thinking and education.